Lawn boy : a novel - Evison, Jonathan (Algonquin Books of Chapel Hill, 2018)
"Mike Muñoz is a young Mexican American not too many years out of high school--and just fired from his latest gig as a lawn boy on a landscaping crew. Though he tries time and again to get his foot on the first rung of that ladder to success, he can't seem to get a break. But then things start to change for Mike, and after a raucous, jarring, and challenging trip, he finds he can finally see the future and his place in it"--